Macroeconomic factors of Ukrainian currency instability during the global financial crisis - Peters, Alona (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The article discusses the macroeconomic factors influencing Ukraine’s currency instability in conditions of the global financial crisis. These factors include the slow-down in the economies of countries that are major trading partners of Ukraine, the decrease in world market prices and demand for the products of the chemical industry and metallurgy which are part of Ukrainian exports, rising prices for imported gas and oil, growth of external debt, significant excess of imports over exports, negative balance of payments, high dollarization of the economy and low level of confidence in the Ukrainian currency, the rapid decrease in foreign exchange reserves, high dependence on imported oil and gas from Russia.
Keywords: Ukraina; niestabilność waluty; czynniki makroekonomiczne; kryzys finansowy